Compact City-Sprawl City: two interacting urban forms - Frediani, Julieta Constanza (2008)
From the perspective of mobility relation-city design, the automobile is placed at the center of the problematic dichotomy compact city/ sprawl city. This paper analyses the role of transport as one of the factors which generates unsustainability in urban areas associated with mobility and the exponential growth in car usage and distance travelled. Within this framework, this work supports the hypothesis that the higher energy consumption produced by transport depends on the forms adopted by urban expansion. Hence, a highly consolidated urban network allows higher energy saving than a spreading urban network which generates higher mobility and, thus, higher energy consumption. Previous considerations prove the need for a systematic approximation to compact or sprawling urban growth to verify our hypothesis. This hypothesis stems from some previous considerations: the focus on the area of analyses on energy saving, the absence of coordination between transport and population location and their activities, and the limited treatment of urban network characteristics in studies referred to energy saving in houses. Although international forums have been taking the problem of compact city/sprawl city as fundamental in discussions on urban growth, the absence of precision in the definitions of 'compact' and ‘diffuse’ is confirmed. Hence, the need for asking about the factors related to population mobility which determine the sustainability or lack thereof in both urban forms. The methodological approach to address this problem coordinates housing and mobility variables considered from two urban growth representative forms: compact and sprawl. Five areas situated in La Plata (Buenos Aires Province, Argentina) are compared. Three are located in the outskirts and two in the central area. The population socio-economic level, the consolidation and structuring of each area, and the housing energy consumption per area are considered.